Is there a difference between capsule endoscopy and computed tomography as a first-line study in obscure gastrointestinal bleeding? - Jeon, Seong Ran; Jin-Oh, Kim; Hyun Gun, Kim; Tae Hee, Lee; Jun-Hyung, Cho; Eui Ju, Park; Dae Seop, Lim; Wan Jung, Kim; Bong Min, Ko; Joo Young, Cho; et al. (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Capsule endoscopy (CE) is currently recommended as the first-line study in the evaluation of obscure gastrointestinal bleeding (OGIB), while computed tomography (CT) is often thought of as complementary to CE. This study evaluated CT as a first-line study in OGIB and compared it with CE. Materials and Methods: Ninety-nine patients with OGIB who received both CE and CT were included. CT included conventional CT and CT enterography (CTE). Patients were divided into two groups: the CT before CE group (CT first group; n=75) and the CE before CT group (CE first group; n=24). The two groups were compared retrospectively. Results: Overt OGIB was present in 92% of patients. Mucosal lesions (46%) were the most common diagnoses, while tumors accounted for 7%. The diagnostic yield of CE was significantly higher than that of CT for both groups (CT first group, p<0.001; CE first group, p=0.013). In the CT first group, the diagnostic yield using both CT and CE (48/75; 64%) was significantly higher than that for CT alone (12/75; 16%, p=0.005). In the CE first group, the diagnostic yield with both CT and CE versus CE alone was 70.9% versus 62.5%, respectively, with a significant difference (p=0.045). Conclusion: There was no significant clinical difference associated with the order in which the tests were performed. However, CE and CT, when used together, had a significantly greater diagnostic yield than did CE or CT when used alone.